EXPERIMENTAL MACROECONOMICS, A CHALLENGE FOR THE FUTURE? - Helena Chytilova (European Scientific Journal, ESJ, 2014)
Standard econometric approaches have been many years a well-established workhorse in economic research. However, widespread application of macroeconomic models with explicit micro-foundations since rational expectations revolution in 1970 gave birth to experimental macroeconomics recently, where controlled environment might be used to get insights regarding the effects of alternative institutions and policies with direct implications at the aggregate level. This article aims to enrich present discussion about appropriateness of this method, since a very few studies deal with this new phenomenon among others Ricciuti (2008), Duffy (1998). We claim that experimental macroeconomics shouldn´t be omitted as one of the possible methods in economics, since individual and aggregate outcomes might be assessed. As a result, it should represent complement to standard econometric techniques. Furthermore, illustrative case study is used to demonstrate that macroeconomic experiments are not a distinct ones from microeconomic ones and represent powerful instrument for evaluation of micro-founded macroeconomic models.